PENERAPAN DIVERSI DALAM PENANGANAN TINDAK PIDANA YANG DILAKUKAN ANAK DI POLRES SEMARANG - Hartono Hartono (Jurnal Pembaharuan Hukum, 2015)
Actions taken by the Police Semarang in dealing with criminal offenses committed by children that is of a criminal offense of theft committed by children, is through the diversion, the thought of giving authority to the law enforcement officers to take measures wisdom in handling or resolving problems offense children by not taking a formal way among others to stop or discontinue / release of the criminal justice process or return/hand over to the public and other forms of activities of other social services. Implementation of diversion itself can actually be done at all levels, namely examination of the investigation, prosecution, examination at trial to the stage of the implementation of decisions. This implementation is intended to reduce the negative impact of children’s involvement in the judicial process. In the investigation of the child in the case of juvenile delinquents in Semarang Police carried out by investigators of the Child, established by the Decree of the Head of the Indonesian National Police or an officer designated by him. Thus Investigator General can not conduct an investigation of a case brat, except in certain cases, such as child investigator yet in place